Dinamika Pencatatan Pernikahan Di Indonesia dalam Kajian Maslahah Mursalah - Yusmita, Yusmita (Institut Agama Islam Negeri (IAIN) Curup, 2023)
The purpose of this study is to answer how the application of mashlahah mursalah in marriage registration in Indonesia. The method in this study is a library method by reading books or magazines with other data sources in the library. In an axiological review, marriage registration is carried out to establish marriage order in society. It attempts to protect the dignity and sanctity of marriage, and more specifically women in domestic life. Through marriage registration as evidenced by a marriage certificate, each husband and wife get a copy. If in the future there are disputes and disputes between them, or one is not responsible, then the other can take legal remedies to defend or obtain their respective rights. This marriage registration brings great benefits to Muslims in Indonesia, especially women, especially wives. Jumhur fuqaha agreed that maslahat is acceptable in Islamic jurisprudence. All benefits must be taken as a source of law as long as they are not motivated by the impulse of lust not and do not contradict the nash and maqasid as-shari'. The mashalih mursalah is among the things discussed. One of the legal provisions based on maslahat mursalah is the necessity of marriage registration in KUA for Muslims in Indonesia